The 30 day MBA in international business : your fast track guide to business success - Barrow, Colin, 1941- (Kogan Page, 2016)
"As domestic business becomes increasingly reliant on succeeding in export markets, the need for specialist knowledge in international trade is crucial. With thorough explanations of the current business environment, brand new case studies, and packed with links to free online resources, the second edition of The 30 Day MBA in International Business covers international marketing strategy, managing international organizations, selecting global strategic partners, finance, accounting, and human resource management. This book will help managers, aspiring managers, and business students understand export trading to the benefit of their businesses. "--Resumé vydavatele